Impact Of Liquidity Risk, Solvency Ratio And Corporate Governance To The Sukuk Defaulted Firm - Wan Hasmanirah Binti Wan Mohammad
Sukuk default issue has impressed many parties of the sukuk industry, especially after the global financial crisis in 2007-2008 based on several high-profile cases reported related to sukuk near-default in 2009 which involved some Gulf Cooperation Council (GCC) countries and the United States of America (US), such as Saad Group Golden Belt Sukuk (Saudi Arabia), the Kuwaiti Investment Dar Sukuk (Kuwait), and the East Cameron Gas Company Sukuk (US). In Malaysia, there were 35 sukuk issuer firms registered default by Rating Agency Malaysia Berhad (RAM) and Malaysian Rating Corporation Berhad (MARC) from 2002 to 2014. Failure to address the issue may affect the banking and financial institutions in the sukuk issuance countries. Malaysia as the prime sukuk issuer in the world has issued sukuk for financing the industries and sectors in constructions, development and investment. Therefore, it is timely for researcher to do research on the sukuk default. This study investigates the extent to which liquidity risk, solvency ratio and corporate governance contribute to the characteristics of 30 sukuk default and 30 non-default firms in Malaysia from 2006 to 2011. In order to understand sukuk default, three independent variables are tested which are liquidity risk, solvency ratio and corporate governance. Liquidity risk is measured by using quick ratio and cash to asset ratio, solvency ratio is measured by using interest coverage ratio and debt to equity ratio, whereas the corporate governance is measured by using existence of audit committee and independent director. The analyses are conducted on SPSS and WEKA by using logistics regression and decision tree analysis. From the findings of each independent variable, the liquidity risk (quick ratio and cash to asset ratio), solvency ratio (debt to equity ratio) and corporate governance (existence of audit committee) contributed to the sukuk default and defaulted sukuk firms. Meanwhile, the full model, finding from WEKA revealed that existence of audit committee, debt to equity ratio and quick ratio affect sukuk default and sukuk defaulted firms. Therefore, from the findings, it shows that liquidity risk, solvency ratio and corporate governance contributed to the sukuk default and sukuk defaulted firms in Malaysia from 2006 to 2011. This findings indicate that sukuk default and sukuk defaulted firms coincided with world financial crisis of 2007-2008. Future research is suggested on the need to explore more on the sukuk, liquidity risk, and financial crisis.